DNA barcoding and genetic variation in caged pangasiids in Pahang River Basin - Akbar, John; Jalal, K. C. A.; Mohd Asri, Ummu Nasuha; Nordin, Noor Faizul Hadry; Ambak, Mohd. Azmi (Universiti Teknologi Malaysia, 2015)
The domestication aquaculture selection in farm environment can cause changes in phenotype and genotype of farmed fishes, which may later influence the demographic structure of wild populations if they accidentally escaped from cages. This is an alarming situation for conservation of native species of Pangasius sp. in Pahang River. Hence, the present study was aimed to investigate genetic variation among the fishes collected from different cages from Pahang River. We adopted conventional taxonomical approach to identify species and cross-examined using universal barcode gene Cytochrome Oxydase Subunit 1 (COX1) gene. Samples were collected from 6 commercial cages from Pahang River. Haplotype and genetic diversity among the fishes from different cages were determined. Results from Neighbor Joining tree showed that most of the samples were identified to be Pangasianodon hypothalamus despite having different morphometric character. This study also revealed that most of the caged Pangasius cultured in Pahang River are exotic and non-native to Malaysia. Thus, a continuous monitoring through studies on genetic variation of Pangasius sp. is an essential need for the sustainable development of this endangered fishes in Pahang River.